Improving Accounting Skills Through Online Learning: The Role of Basic Accounting Websites (Bacsite) - Liana Fahrunisa; Gunahardi; Sri Sumaryati (Jurnal Teknologi Pendidikan)
The gap between accounting graduates' competencies and industry demands is still a challenge, especially when it comes to financial report preparation skills. In the era of digital transformation, future accountants are also required to have sexual skills with the demands of the industry. This research explores the effectiveness of Bacsite (Basic Accounting Website) as a learning medium in improving participants' accounting skills. This research used a pre-test and post-test-based experimental method in the control group and the experimental group, the results showed that participants who used Bacsite experienced a 59% higher increase in accounting skills scores than the control group which only increased 54%.